Partially bio‐based aromatic polyimides derived from 2, 5‐furandicarboxylic acid with high thermal and mechanical properties. Issue 10 (22nd February 2018) - Ma, Kai; Chen, Guofei; Wang, Wei; Zhang, Anjiang; Zhong, Yingying; Zhang, Yajie; Fang, Xingzhong
ABSTRACT: Two novel bio‐based diamines are synthesized through introduction of renewable 2, 5‐furandicarboxylic acid (2, 5‐FDCA), and the corresponding aromatic polyimides (PIs) are then prepared by these diamines with commercially available aromatic dianhydrides via two‐step polycondensation. The partially bio‐based PIs possess high glass transition temperatures ( T g s) in the range from 266 to 364 °C, high thermal stability of 5% weight loss temperatures ( T 5% s) over 420 °C in nitrogen and outstanding mechanical properties with tensile strengths of 79–138 MPa, tensile moduli of 2.5–5.4 GPa, and elongations at break of 3.0–12.3%. Some colorless PI films (PI‐1‐b and PI‐1‐c) with the transmittances at 450 nm over 85% are prepared. The overall properties of 2, 5‐FDCA‐based PIs are comparable with petroleum‐based PI derived from isophthalic acid, displaying the potential for development of innovative bio‐based materials. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 1058–1066 Abstract : Two series of novel, partially bio‐based aromatic polyimides (PIs) derived from two new 2, 5‐furandicarboxylic acid‐based diamines are synthesized. These PIs possess excellent properties such as high glass transition temperatures, good transparency and outstanding mechanical properties, which are comparable with the petroleum‐based PIs derived from isophthalic acid. They display potential as alternatives to petroleum‐based high performance resins. This work contributes to the rapid development of renewable and bio‐based polymers.